Accompaniment needs of nursing students related to the dying patient - D Van Rooyen; R Laing; WJ Kotzé (AOSIS, 2005)
Nurse educators are responsible for accompanying students towards becoming capable, competent professional nurses who are a credit to themselves, their patients, colleagues and profession. Student nurses need, therefore, to be taught to render comprehensive nursing care to patients in all stages of their lives, including when they are dying. Being confronted with human suffering and death is challenging and traumatic. Those exposed to such events on a daily basis need to have a solid foundation of self preservation to see past the pain of suffering and to bring light and hope to those in need. A young student nurse will only experience positive growth and development in these circumstances if she is also cared for and guided with understanding. The researcher utilized a qualitative, explorative, descriptive and contextual design based on the phenomenological approach to enquiry. The following question was asked at the beginning of each unstructured phenomenological interview: "How was if for you to care for a dying or deceased patient?" The central theme identified that student nurses experience turmoil in their different relationships in their accompaniment of the dying patient. Guidelines based on the central theme and sub-themes that emerged from raw data, as well as literature, are offered as strategies to promote/enhance optimal accompaniment of student nurses caring for the dying patient.